2014
DOI: 10.4137/ehi.s15256
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Exercise for Control of Occupational Neck/Shoulder Disorders a Review of Prospective Studies

Abstract: A review was conducted of prospective studies (1997–2014) examining the efficacy of exercise as a workplace intervention to control neck/shoulder pain, symptoms, and disability. The review identified 38 relevant studies – 20 were classified with positive effects, 13 with null effects, and 5 as inconclusive. Of the positive studies, 12 were consistent with Level I evidence, 3 with Level II evidence, and 5 with Level IV evidence. Specific resistance training (SRT) exercise appeared to be associated with more pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 67 publications
(243 reference statements)
0
32
0
3
Order By: Relevance
“…Both the positive effects on musculoskeletal pain and the effects on body composition and wellbeing could represent unspecific reactions to regular exercise. Such effects have been reported in a number of review articles (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 95%
“…Both the positive effects on musculoskeletal pain and the effects on body composition and wellbeing could represent unspecific reactions to regular exercise. Such effects have been reported in a number of review articles (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 95%
“…There is strong evidence of the effectiveness of strength training at the workplace for reducing musculoskeletal complaints in specific regions of the body [2024]. A variety of strength training protocols are described in the literature, including protocols to decrease pain in the cervical, lumbar, and shoulder areas; low-intensity training; high-intensity training with concentric contractions; high-intensity training with isometric contractions; and highly intensive training (HIT) [2022, 25]. However, there is consensus that resistance exercises are more effective [20, 25], and 20-min training sessions [2025] 3 times a week for periods of 10 weeks or more [20, 23] reduce musculoskeletal complaints in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of strength training protocols are described in the literature, including protocols to decrease pain in the cervical, lumbar, and shoulder areas; low-intensity training; high-intensity training with concentric contractions; high-intensity training with isometric contractions; and highly intensive training (HIT) [2022, 25]. However, there is consensus that resistance exercises are more effective [20, 25], and 20-min training sessions [2025] 3 times a week for periods of 10 weeks or more [20, 23] reduce musculoskeletal complaints in the workplace. The protocol of heavy resistance exercise at the workplace includes exercise with higher intensity in eccentric and concentric contractions, using dumbbells, elastic bands, and exercises against gravity [20].…”
Section: Introductionmentioning
confidence: 99%
“…The SBP was focused on the neck, shoulders, back, and upper extremities (hands and wrist) and not specifically on the hamstring muscles, hips or lumbosacral regions; this design may explain why the program had no effect on the flexibility of these regions. Lowe and Dick (2015) suggested that the effect of workplace exercise is minimal and effective as tertiary prevention and therapeutic relief of neck/shoulder symptoms. Moreover, previous studies have demonstrated that specific exercise programs improves strength and resistance levels of the trunk and lumbar extensors (Andersen et al, 2012;Carvalho Mesquita, Ribeiro, & Moreira, 2012;Koumantakis, Watson, & Oldham, 2005), and these improvements appear after 6 to 8 months (Cohen, Goel, Frank, & Gibson, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Stretch breaks in the work setting improve flexibility and grip strength and reduce musculoskeletal complaints and these motions can cause cumulative trauma disorder (Dick, Graveling, Munro, & Walker-Bone, 2011, Lowe & Dick, 2015. These activities lead to muscle imbalance, which results in a mechanical disadvantage and weakness.…”
Section: Original Article (Full Paper)mentioning
confidence: 99%